2013
DOI: 10.1111/epi.12430
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy in TSC: Certain etiology does not mean certain prognosis

Abstract: SUMMARYPurpose: Prevalence and long-term outcome of epilepsy in tuberous sclerosis complex (TSC) is reported to be variable, and the reasons for this variability are still controversial. Methods: We reviewed the clinical characteristics of patients with TSC who were regularly followed since 2000 at the San Paolo Multidisciplinary Tuberous Sclerosis Centre in Milan, Italy. From patient charts we collected data about age at epilepsy onset, seizure frequency and seizure type, history of infantile spasms (IS), epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
68
3
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(80 citation statements)
references
References 24 publications
7
68
3
1
Order By: Relevance
“…Type and severity of seizures, especially infantile spasms, along with early age of seizure onset also appear to be associated with increased likelihood of cognitive and behavioral difficulties particularly if seizures are not controlled [812]. Similar associations have been reported for higher risk for ASD in TSC [9, 1315], and it has been suggested that epilepsy may be an independent predictor of intellectual ability in TSC [7, 10, 16].…”
Section: Introductionmentioning
confidence: 90%
“…Type and severity of seizures, especially infantile spasms, along with early age of seizure onset also appear to be associated with increased likelihood of cognitive and behavioral difficulties particularly if seizures are not controlled [812]. Similar associations have been reported for higher risk for ASD in TSC [9, 1315], and it has been suggested that epilepsy may be an independent predictor of intellectual ability in TSC [7, 10, 16].…”
Section: Introductionmentioning
confidence: 90%
“…; Vignoli et al . ). The cortical lesions seen in TSC contribute to epileptogenesis, and it is hypothesised that inactivating mutations lead to increased mTOR kinase signalling and likely changes in parallel signalling pathways (Karbowniczek et al .…”
Section: Introductionmentioning
confidence: 97%
“…Epilepsy is seen in most patients with TSC, with published prevalence reported as 72.5% (Vignoli et al . ) and 84% (Kingswood et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…6 There are several therapeutic options available for the treatment of focal seizures and infantile spasms associated with TSC including antiepileptic drugs (AEDs), hormonal therapy, epilepsy surgery, ketogenic diet, and vagus nerve stimulation. 1,2,8,9 Most of these studies were retrospective in nature, reported a single-center cohort, and had relatively small sample size. 6,7 The natural history of epilepsy in TSC has been evaluated in only a handful of studies.…”
Section: Introductionmentioning
confidence: 99%